Bond Strength of Steel Bars in Sustainable Concrete Made with Recycled Aggregates - Panumas Saingam; A.J. Min; Ali Ejaz; Qudeer Hussain (Key engineering materials, 2023)
Lately, considerable efforts have been directed towards investigating the practicality of using coarse recycled concrete aggregate as a potential substitute for natural coarse aggregate (NCA) in concrete construction. Research has shown that both the proportion of replacement and the properties of recycled aggregates play a significant role in affecting the tensile strength, compressive strength, and bonding characteristics of concrete. In certain cases, recycled aggregate concrete exhibits lesser mechanical properties when compared to concrete made with normal aggregates. The current study investigated the performance of Sika AnchorFix-1 to enhance the bond strength between steel bars and recycled aggregate concrete. The findings suggest that Sika AnchorFix-1 successfully prevented the concrete rupture in the case of concrete with recycled concrete aggregates, whereas concrete rupture could not be prevented in the case of concrete with recycled brick aggregates. Hence, a lower bond strength was obtained for specimens with recycled bricks aggregates than specimens with recycled concrete aggregates.
Keywords: Recycled Aggregate Concrete Performance; Innovative concrete reinforcement materials; Innovations in Concrete and Construction Materials